Determination of specific iron chelator by using LC-ICP-MS and LC-ESI-MS - Mohamed, Khairul Nizam; Martha, Gledhill (Elsevier, 2015)
Identification and quantification of siderophore type chelate was undertaken using recently developed high-performance liquid chromatography-mass spectrometry methods. Five different siderophore type chelates were detected and the compounds comprised of two groups; ferrioxamines. In the dissolved phase, three types of hydroxamate siderophore have been identified; Ferioxamine B (FOB), Ferrioxamine G (FOG) and ferrioxamine E (FOE). Concentration of dissolved FOB, FOG and FOE are extremely low between 0–135 x 10 -18 M, and their distribution is spatially and temporally variable in this region. The concentration and diversity of siderophore type chelates determined during this study, was lower than those reported previously for dissolved ferrioxamine siderophore concentrations at lower latitudes in the Atlantic Ocean. The initial data from this study suggested that dissolved siderophores in this region is not an important fraction (< 0.1%) of the natural organic Fe(III) binding ligand pool.